2013
DOI: 10.1097/bsd.0b013e318292aad7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Axial and Anterior Interbody Fusions of the L5–S1 Segment

Abstract: The radiographic success and adverse events associated with AxiaLIF appear to be similar to that observed for ALIF, suggesting that this technique represents a safe and effective method for achieving an interbody fusion across the L5-S1 disk space when utilized in conjunction with posterior fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…9, 31 The overall pseudarthrosis rate at L5-S1 following axial interbody arthrodesis was 6.9% (95% CI 1.0%-16.2%). Failed fusion was verified by CT in 12 of the 15 studies and by radiography in the remaining 3 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9, 31 The overall pseudarthrosis rate at L5-S1 following axial interbody arthrodesis was 6.9% (95% CI 1.0%-16.2%). Failed fusion was verified by CT in 12 of the 15 studies and by radiography in the remaining 3 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Only a single article comparing axial interbody fusions and another interbody fusion technique was identified. 31 Because no other comparative studies were identified, that single comparative article was treated as a case series, and only patients from the Axialif arm were included in our systematic review. All reported complications were noted, including pseudarthrosis at L5-S1, revision and/or subsequent surgery, infections, postoperative radiculopathy, neurological deficits, bowel perforations, retroperitoneal hematomas and/or vascular injury, and significant medical complications (for example, myocardial infarction, stroke, and so forth).…”
Section: Data Extractionmentioning
confidence: 99%
“…This finding was challenged by results of a recent retrospective study by Yi et al, which reported no significant difference in the rate of fusion for 36 patients who underwent axial lumbosacral interbody fusion or TLIF 40) . Similarly, two retrospective analyses comparing axial lumbosacral interbody fusion to ALIF reported no significant difference in fusion rates for the approaches 37,41) . The Oswestry Disability Index (ODI) and Visual Analogue Scale (VAS) are validated, vigorous condition-specific outcome measures used in the management of spinal disorders to assess function and back pain, respectively 42) .…”
Section: Resultsmentioning
confidence: 96%
“…6,23,24 The Roy-Camille lateral mass screw-plate technique was introduced into the US by Paul Cooper, M.D. 1,4,8,9,12,14,16,22,26 Despite this vast clinical experience, no system has been approved by the Food and Drug Administration (FDA) for "on label" usage in the subaxial cervical spine for the specific purpose of lateral mass fixation. 7,9 In the 1990s, second-generation plating systems emerged, which allowed more versatility in screw position through the plate holes.…”
Section: Lateral Mass Screw Fixation In the Cervical Spinementioning
confidence: 99%